2019
DOI: 10.47102/annals-acadmedsg.v48n8p247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Knowledge and Attitudes on Lifestyle Practices in Preventing Type 2 Diabetes Mellitus

Abstract: Introduction: Diabetes mellitus is a major public health issue in Singapore. To shape healthcare policies for the primary prevention of diabetes, it is crucial to understand Singaporeans’ knowledge, attitudes and practices related to diabetes and its prevention. This study aimed to assess the knowledge, attitudes and lifestyles of individuals without diabetes. Materials and Methods: A cross-sectional household survey was performed between 31 January to 3 February 2019 to examine knowledge, attitudes and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
3
0
4
Order By: Relevance
“…Our findings align with a local study that showed high awareness of diabetes and perceived efficacy of preventative behaviours and shed some light on why actual uptake of these behaviours may be low despite the high knowledge [ 11 ]. Perceived severity of diabetes comes from the downstream complications of the later stages of T2D, which seem to be distant for those without T2D.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings align with a local study that showed high awareness of diabetes and perceived efficacy of preventative behaviours and shed some light on why actual uptake of these behaviours may be low despite the high knowledge [ 11 ]. Perceived severity of diabetes comes from the downstream complications of the later stages of T2D, which seem to be distant for those without T2D.…”
Section: Discussionsupporting
confidence: 88%
“…A household survey in 2019 found that 86% and 89% of participants agreed that healthy eating and exercise respectively, can control the risk of diabetes. However, only 37% ate the recommended 5 servings of fruits and vegetables, and 28% met HPB’s physical activity recommendation of 150 min/week [ 11 ]. To reach higher engagement in T2D prevention, the discrepancy between knowledge and practice needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Houve predomínio de inativos que vivem com companheiro e, destaca-se a importância da figura do companheiro como contribuição para um ambiente de apoio no manejo do diabetes (8) .…”
Section: Discussionunclassified
“…Observa-se na literatura nacional e internacional, que os estudos sobre as atitudes psicológicas em diabetes tipo 2 demonstram que as pessoas enfrentam dificuldades para conviver com a condição, predominando emoções como a tristeza, o desgosto e a raiva diante do enfrentamento do diabetes, além do medo das complicações agudas e crônicas (3,4,6,7) . Quando conhecem suas próprias emoções o suficiente, as pessoas são capazes de contornar situações de estresse para fazer escolhas seguras e sentirem-se confortáveis em relação a sua condição crônica (8) .…”
Section: Introductionunclassified
See 1 more Smart Citation